Blood and biochemical changes caused by bee venom-nanoemulsions; a study on animal arthritis model - Yaser Yousefpoor; Amir Amani; Seyyed Mohammad Hashemi; Ali Afgar; Seyed Mohammad Amini; Mohamad Javad Mirzaei-Parsa (Nanomedicine Journal, 2024)
Objective(s): Traditionally, Bee venom (BV) is used through stinging or injection to treat rheumatoid arthritis (RA). This study aimed to assess the side effects of local bee venom nanoemulsions (BV-NEs) in the collagen-induced arthritis (CIA) model by examining biochemical and hematological parameters. Materials and Methods: The BV-NEs were prepared, and the CIA model was induced in rats. After the seventh day, the groups were locally treated for two weeks as the following: blank (free treatment), negative control (NE-0), positive control (hydrocortisone acetate ointment 1%, 50 mg/day), BV control (37.5 µg/ml/day), and BV-NEs receiving 75, 37.5, 18.75, and 9.37 µg/ml/day. Three steps of blood sampling were done on days 0, 7, and 21 (healthy rats, before treatment, and at the end of treatment, respectively).Results: The results revealed that blood levels of Glucose, Cholesterol, Urea, Aspartate aminotransferase (AST), Alkaline phosphatase (ALP), White blood cell (WBC), and %Neutrophil significantly increased before the treatment. Nevertheless, most parameters declined at the end of the treatment compared to the blank and negative control groups about BV-NEs dose-dependently. The drastic changes in biochemical parameters in the CIA model indicated the effect of the immune system function on the metabolic system. Also, NE’s impact of BV passed through the skin on these items. Conclusion: BV-NEs can reduce inflammation caused by arthritis without acute adverse effects on the routine biochemical and hematological parameters.